Gay homoconjugality in Portugal: a case study - Santos, F. (Congreso Universitario Internacional sobre la Comunicación en la Profesión y en la Universidad de Hoy : Contenidos, Investigación, Innovación y Docencia, CUICIID 2018, 2018)
Based on a qualitative interview of a non-heterosexual young men living in homoconjugality, the article aims to analyze his biographical pathway, his expectations, representations, values and the way in which these variables intersect and shape the conjugal and family dynamics. The findings reveal that the variables mentioned above come together with homophobia, heteronormativity and others structural constraints of Portuguese society to configure the conjugal relationship and both the conjugal and parental transition. Nevertheless, this is a case study that aims to shed light to the importance of the individual. Because, in Cardenal words "the social is inscribed in the individual" and vice-versa.